Pengaruh Kompetensi Sumber Daya Manusia dan Motivasi Kerja terhadap Kinerja Pegawai pada PT Bank SUMUT Medan - Via Ervilia; Siti Wardah Pratidina Nasution; Riny Viri Insy Sinaga (Universitas Warmadewa, 2025)
Human resources are a key factor that determines the success of a company's operations and business in achieving its goals and targets. This study was conducted to analyze the influence of human resource (HR) competence and work motivation on employee performance at PT Bank Sumut Medan. This research uses a research approach with quantitative analysis with a survey method. The population in this study were 43 employees of PT Bank Sumut Medan, who were the samples in this study. Data analysis used multiple regression techniques. The results of the study showed that Human Resource Competence did not have a significant effect while Work Motivation had a significant effect on Employee Performance at PT Bank Sumut Medan. Human Resource Competence and Work Motivation simultaneously had a significant effect and had a very strong contribution of 91.8 percent on Employee Performance at PT Bank Sumut Medan.